A new statistical ranking of tree inception voltage distribution of silicone rubber and epoxy resin under AC voltage excitation - Ahmad, Mohd. Hafizi (Praise Worthy Prize, 2011)
Electrical treeing is a common insulation pre-breakdown phenomenon. Due to prolonged stresses, polymeric insulating material cannot withstand the aging and degradation from voltage application, environmental factors and from several influenced factors. Therefore, this phenomenon needs to be explored from the initial stage for better understanding of its early inception. However, previous studies have shown that some initial parameters were analysed by using still-can-improved statistical techniques. Thus, in this paper, a more accurate statistical technique was performed in order to determine the value, the distribution and distribution statistical rank of tree inception voltage of silicone rubber and epoxy resin by fitting method. The electrical tree inception voltage was measured and recorded by applying a sequential of AC voltage between the point-to-plane electrodes via a camera-equipped online monitoring system. The experiment was performed based on IEC 1072:1991 "Methods of Test for Evaluating the Resistance of Insulating Materials Against the Initiation of Electrical Trees". The experimental results were analysed satistically and comparison was made between the best fitted distribution and Weibull distribution. Obtained results have shown that tree inception voltage depends on the material composition since other factors were kept constant. Based on the statistical analysis, the tree inception voltage of silicone rubber and epoxy resin were best fitted with Johnson S B distribution rather than Weibull distribution which showed higher fitting error. Based on the fitted distribution, the values of tree inception voltage of silicone rubber and epoxy resin were calculated and found to be 3.1529 kV and 4.6528 kV respectively. The results of fitting using Anderson-Darling goodness-of-fit test and Kolmogorov-Smirnov goodness-of-fit were compared. It was found that the Johnson S B statistical distribution holds good for silicone rubber and epoxy resin for electrical treeing initiation. Therefore, it has been proved that Johnson S B distribution is better than Weibull distribution in representing the tree inception voltage distribution.